008 Principles for the Development of Specialty Society Clinical Guidelines. (15th August 2013) - Fulda, G; Wolfkiel, C; Begolka, W Smith; Campos-Outcalt, D; Groman, R; Rubin, K; Davidson, C; May, C; Starkey, M; Qaseem, A
Abstract : Background: In 2011 the Institute of Medicine (IOM) issued a report "Clinical Practice Guidelines We Can Trust" and "Standards for Systematic Reviews". These documents represent an idealised approach to guideline development. The Council of Medical Specialty Societies (CMSS) was challenged to provide leadership on a pragmatic pathway for developing "Trustworthy" guidelines. CMSS representing 38 societies and the Clinical Practice Guideline (CPG) group is the largest of nine component groups. Context: The IOM Trustworthy report contains 20 standards addressing transparency, conflict of interest and other recommendations. Guidelines International Network (GIN) published a set of 11 key components for high quality and trustworthy guidelines. Reconciling and applying these standards is challenging for specialty societies who by their very nature may be insular and sometime resource limited. Description of Best Practice: The CPG writing group including representatives from AAD, AAFP, AANS AAP, ACC, ACP, ACOEM and SCCM developed a set of 80 principles that were approved as policy by the CMSS Board in late 2012. These Principles include areas that a specialty society should, must or may consider in developing their own guidelines development methodology. Lessons for Guideline Developers, Adaptors, Implementers, and/or Users: These areas correspond to those outlined by the IOM and GIN but are intended to detail more specific issues that specialty societies are confronted by such as balancing panel expertise and potential bias. The overriding CMSS concepts include a practice approach to extensive evidence review, transparent conflict of interest management and broad stakeholder involvement. The CMSS Principles are intended to be interpreted transparently by member societies developing clinical practice guidelines.